The European Green Deal – a Feasible Ambitious Initiative? Array - Pîrvu, Elena Loredana (Journal of Danubian Studies and Research, 2020)
THE EUROPEAN GREEN DEAL is an EU initiative to make Europe the first climate neutral continent by 2050. This plan, proposed for the first time in the history of the Community, is a revolutionary, strategic and legislative one and will have a significant impact on the European economy and society. Given that current energy and climate forecasts show that emissions can only be reduced by 60% by 2050, reaching the objective of this deal (transforming Europe into a climate neutral continent) will be the greatest challenge of the European Union. This deal proposes a set of 47 actions, the main element of this deal being the Climate Neutrality Law, setting the year 2050 as a goal and direction for all EU policies, offering probability/predictability to all citizens, companies and public authorities. This deal aims to make Europe abandon classical energy in the coming decades and switch entirely to clean energy.